2015
DOI: 10.1002/2015ja021690
|View full text |Cite
|
Sign up to set email alerts
|

Broadband low‐frequency electromagnetic waves in the inner magnetosphere

Abstract: A prominent yet largely unrecognized feature of the inner magnetosphere associated with particle injections, and more generally geomagnetic storms, is the occurrence of broadband electromagnetic field fluctuations over spacecraft frame frequencies (fsc) extending from effectively zero to fsc ≳ 100  Hz. Using observations from the Van Allen Probes we show that these waves most commonly occur premidnight but are observed over a range of local times extending into the dayside magnetosphere. We find that the varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
135
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(149 citation statements)
references
References 77 publications
14
135
0
Order By: Relevance
“…It has been shown that the observed broad spectrum of low-frequency electromagnetic field variations in the inner magnetosphere are well modeled as an ensemble of eigenmodes or KFLRS with form [Chaston et al, 2014]. It has been shown that the observed broad spectrum of low-frequency electromagnetic field variations in the inner magnetosphere are well modeled as an ensemble of eigenmodes or KFLRS with form [Chaston et al, 2014].…”
Section: 1002/2017gl074587mentioning
confidence: 97%
See 4 more Smart Citations
“…It has been shown that the observed broad spectrum of low-frequency electromagnetic field variations in the inner magnetosphere are well modeled as an ensemble of eigenmodes or KFLRS with form [Chaston et al, 2014]. It has been shown that the observed broad spectrum of low-frequency electromagnetic field variations in the inner magnetosphere are well modeled as an ensemble of eigenmodes or KFLRS with form [Chaston et al, 2014].…”
Section: 1002/2017gl074587mentioning
confidence: 97%
“…Figure 2c shows E ϕ in the wave frame as well as the trajectories of resonant electrons (white curves) at a number of equatorial pitch angles (α). E ϕ is given by the solution of equation (3) for k ϕ ρ i = 1 at the equator for the plasma model presented in Figures 2a and 2b [Chaston et al, 2014] above an infinitely conducting ionosphere. Alternate conductivity models or plasma profiles could also be used without changing the substance of the following discussion.…”
Section: 1002/2017gl074587mentioning
confidence: 99%
See 3 more Smart Citations